Statistics Self-Efficacy And Learning Styles As Predictor Of Statistics Anxiety (International Journal of Scientific Research and Management (IJSRM), 2018)
The study investigated statistics self-efficacy and learning styles as predictors of statistics anxiety among graduate students in University of Port Harcourt. Seven research questions and six null hypotheses were formulated to guide the study. The participants in the study were 150 (male = 86, female 64) graduate students drawn through stratified random sampling technique. Three valid instrument titled; statistical anxiety rating scale (STARS), current statistics self-efficacy scale (CSSES), and Grasham Reichann student learning style scales(GRSLSC) was used for data collection. The validity of the instrument was determined using multivariate statistical method of factor analysis. The reliability indices of the instrument were estimated using the Cronbach alpha with coefficients values for statistics anxiety rating scale. .916 and sub scales of .884.71, .80, .70, .63, .60. Current statistics self-efficacy r = .623, and .56, 52, 53, 54, 51, 60 coefficients for the Grasha-Riechmann student learning style scales sub scales. Research question 1, was answered using descriptive statistics of mean and standard deviation, while 2, 3, 4 and 5 was answered using simple and multiple regression. The null hypothesis tested at 0.05 level of significance with ANOVA associated with multiple regression and t – test associated with simple regression was used for providing answers to the null hypothesis. The result revealed that the statistics anxiety level of graduated student was high, Statistics self-efficacy and learning styles both individual and jointly was seen to predict statistics anxiety. It was recommended that psychological and educational intervention be carried out in the context of increasing statistics self-efficacy and reducing statistics anxiety. Based on findings implications were made and suggestions for further studies.